Studying the dynamics of open quantum systems using photons (2017)
We experimentally present the controlled transition, of an open-quantum system, between Markovian and Non-Markovian dynamics. The polarization of light is used as the system, whereas the environment is represented by the spatial structure of light. The controlled coupling of theses two domains is done by a polarization sensitive tunable beam displacer. Additionally, We present the experimental implementation and theoretical model of a controllable dephasing quantum channel using the same photonic variables. Differently, from standard dephasing channels, the channel here reported presents an exotic behavior, in the sense that the evolution of a state, from a pure to a mixed state, shows an oscillatory behavior if tracked in the Bloch sphere.